2010
DOI: 10.1152/ajpgi.00120.2010
|View full text |Cite
|
Sign up to set email alerts
|

miR-802 regulates human angiotensin II type 1 receptor expression in intestinal epithelial C2BBe1 cells

Abstract: Studies have demonstrated that angiotensin II (Ang II) can regulate intestinal fluid and electrolyte transport and control intestinal wall muscular activity. Ang II is also a proinflammatory mediator that participates in inflammatory responses such as apoptosis, angiogenesis, and vascular remodeling; accumulating evidence suggests that this hormone may be involved in gastrointestinal (GI) inflammation and carcinogenesis. Ang II binds to two distinct G protein-coupled receptor subtypes, the AT(1)R and AT(2)R, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 62 publications
(99 reference statements)
0
41
0
Order By: Relevance
“…The results show that DLC1 , ATRX and HFE genes are regulated by miR-200a and miR-200c; DLC1 , HFE and HNRNPA3 are regulated by miR-200b. Although, the changes in the expression of these genes at the mRNA and protein levels after re-expression of miR-200s in H1299 cells were relatively small (<2-fold), such small changes in the expression of microRNA targets are very common (16,53). Despite restoration of normal miR-200 levels, some other components of the post-transcriptional gene silencing pathway in H1299 cells might be in limiting amounts, for example Dicer, which is commonly downregulated in cancer cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that DLC1 , ATRX and HFE genes are regulated by miR-200a and miR-200c; DLC1 , HFE and HNRNPA3 are regulated by miR-200b. Although, the changes in the expression of these genes at the mRNA and protein levels after re-expression of miR-200s in H1299 cells were relatively small (<2-fold), such small changes in the expression of microRNA targets are very common (16,53). Despite restoration of normal miR-200 levels, some other components of the post-transcriptional gene silencing pathway in H1299 cells might be in limiting amounts, for example Dicer, which is commonly downregulated in cancer cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐802 was identified as an important mediator in controlling different pathological process. Intestinal miR‐802 affected the biological efficacy of angiotensin II in gastrointestinal system . In obesity, up‐regulated hepatic miR‐802 impaired glucose metabolism through silencing of Hnf1b .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-802 was characterized as an miRNA that has an important role in the development of lung carcinoma. A previous study demonstrated that miR-802 modulates the biological efficacy of angiotensin II (Ang II) in the human gastrointestinal tract through regulation of the Ang II type 1 receptor expression (14). Furthermore, Kornfeld et al (15) demonstrated that the deregulated expression of miR-802 has a critical role in the development of the obesity-associated impairment of glucose metabolism through targeting of hepatocyte nuclear factor-1β (14).…”
Section: Discussionmentioning
confidence: 99%